Adsorption Potential of Activated Carbon in Some Acidic and Alkaline Media - Badri, M.; Crouse, Karen Anne; Chua, Sook Yan (1990)
An electrode was constructed using activated carbon. Changes in its sUlJace potential were observed when it was dipped into solutions containing HCI and hydroxide and carbonate ofNa +, K + and NH~. These changes have been atlributed to the effect ojconcentration ofCl- and 0 H- ions upon the adsorptive strength ofvariousJunctional groups on the surface oj activated carbon.